Methodological flaws in Aubry, R. L.; Power, G. A. and Burr, J. F.: An assessment of running power as a training metric for elite and recreational runners - Snyder, K. L.; Mohrman, W. P.; Williamson, J. A.; Li, K. (The Journal of Strength and Conditioning Research, 2018)
In the study by Aubry et al., (1) the authors examine the effects of 3 variables: surface, speed, and subject to assess how well "metabolic demand" (p. 1) and "running power" (p. 1) correlate. However, their protocol and analysis contain major methodological flaws that interact to produce misleading conclusions.